The Effect Of Brainstorming Learning Approach On Students’ Critical Thinking Abilities In History Subject In Class X Mia At State High School 10 Palembang - Mialita Mialita; Hudaidah Hudaidah; LR Retno Susanti (Criksetra: Jurnal Pendidikan Sejarah, 2018)
Entitle of this study is “The Influence of Brainstorming Teaching Approaches to The Students’ Critical Thinking Skills in The History Subject of Tenth Graders of Senior High School Number 10 Palembang”. Kind of this study is Experimental Design. The purpose of this study was to determine the influence of Brainstorming Teaching Approaches to The Students’ Critical Thinking Skills. The study had been conducted on February 28th until March 27th, 2017 on four times. This study used one class and the sample of this study were X MIA 1 class as an experimental class. Population of this study is all of students of tenth graders of senior high school number 10 Palembang. Purposive Sampling technique was used to select experimental class as samples of this study. The data of this study were collected by usig test. The statistics which was used to analyze he data in proving the hypothesis was Regresion Test with the real level 0,05.Based on the data analysis of hypothesis testing on the hypothesis Fcount> Ftable, or 12,78 > 4,13. If Fcount> Ftable so reffuse H0. Because Fcount bigger than Ftable, so reffuse H0 and accept Ha. It can be concluded that there was an influence of Brainstorming teaching approaches to the students’ critical thinking skills in the history subject of tenth graders of senior high school number 10 Palembang.